Numerical Simulation Study of Progressive Collapse of Reinforced Concrete Frames with Masonry Infill Walls under Blast Loading. (11th November 2022) - Xu, Qinghu; Zhen, Xuezhi; Zhang, Yu; Han, Mengjun; Zhang, Wenkang
Abstract : The influence of masonry infill walls on the progressive collapse performance of reinforced concrete (RC) frame structures was investigated in this paper, using a nonlinear dynamic analysis approach. Based on ANSYS/LS-DYNA finite element software, two finite element models of RC frame structures with and without masonry infilled walls were established. Then, the collapse modes of the two RC frame structure models were analyzed for different scaled distance blast loads, different locations of column damage, and different span numbers. The results show that with the increase of explosive amount, the collapse degree of the structure is more serious in the same time. Under the condition of destroying the outermost central column, the degree of progressive collapse of the RC frame model with infilled walls in the same time is lower than that of the RC frame model without infilled walls. The RC frame model with infilled walls is more resistant to collapse when the outermost side columns are damaged. With the increase of span number, the structure is more likely to be damaged and collapsed.